Hidden pathways: approaches to understand intra-household gender relations and climate adaptation in Kenya dairy systems - DuttaGupta, Tanaya; Bullock, Renee; Miriti, Philip (International Livestock Research Institute, 2023)
The transformation of livestock systems towards sustainable climate smart systems will generate multiple trade-offs and synergies. In this paper, we describe how gender relations shape, and are shaped by, climate adaptation innovations, specifically the uptake of innovations in dairy producing households in Western Kenya. Our research complements a producer-led scaling intervention in which positive deviants are those who, all else being equal, outperform their neighbours. These ‘adaptation pioneers’ then lead the scaling of climate smart feed and fodder innovations in their communities. However, intra-household dynamics surrounding uptake of innovations often are uneven and can reinforce inequitable distribution of benefits and burdens. We develop a positive deviance framework to identify common and ‘hidden’ patterns and pathways in intra-household gender relations related to dairy innovations, such as decision-making surrounding income and labour. Qualitative data was collected through 20 sex disaggregated focus group discussions, 10 key informant interviews, and field observations in Nandi and Bomet counties over multiple visits in 2022-2023. Using vignettes, we explore what ‘typical’ and less common, or ‘deviant’ household relations are, and whether such deviations are socially acceptable. Thematic analysis was performed in NVivo using iterative deductive and inductive approaches. We find that most households are patriarchal- men are the primary decision-makers and, unsurprisingly, this is generally also socially acceptable in the community. However, both women and men desire more equitable relations and outcomes in their households, but due to social norms that guide what is socially acceptable in the community, these relationships are not discussed openly in society, especially because they undermine men’s roles as heads of household. Married women also negotiate and navigate decision-making spaces, often in hidden ways. This research generates insights into methodological approaches to reveal complex yet oversimplified dimensions of gender relations, such as who has agency, and when and how agency is negotiated. Our findings highlight the potential trade-offs and synergies that may occur through producer-led scaling and sets a foundation for the design of gender responsive scaling approaches that can foster synergies in socially equitable climate adaptation strategies and outcomes.